2008
DOI: 10.1103/physrevb.77.195425
|View full text |Cite
|
Sign up to set email alerts
|

Growth of multilayer ice films and the formation of cubic ice imaged with STM

Abstract: Ice films as many as 30 molecular layers thick can be imaged with scanning tunneling microscopy ͑STM͒ when negative sample biases Ͻ−6͑Ϯ1͒ V and subpicoamp tunneling currents are used. We observe that water deposited onto Pt͑111͒ below 120 K forms amorphous films, whereas metastable cubic ice appears between 120 and 150 K. To determine the mechanisms of ice growth, we investigate the thickness-dependent film morphology. Cubic ice emerges from screw dislocations in the crystalline ice film that are caused by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 36 publications
7
97
0
Order By: Relevance
“…As reported by Kimmel et al (36) and confirmed by our previous STM work (31), water deposited at 135-150 K onto Pt(111) first forms a one-molecule-thin wetting layer (37)(38)(39)(40). Then, isolated 3D ice crystallites emerge and eventually, at thicknesses of ∼3-10 nm, coalesce into a continuous multilayer film.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…As reported by Kimmel et al (36) and confirmed by our previous STM work (31), water deposited at 135-150 K onto Pt(111) first forms a one-molecule-thin wetting layer (37)(38)(39)(40). Then, isolated 3D ice crystallites emerge and eventually, at thicknesses of ∼3-10 nm, coalesce into a continuous multilayer film.…”
Section: Resultssupporting
confidence: 57%
“…We now discuss the growth situation that arises after the 3D crystallites have coalesced into a continuous film. Previously we had shown that the coalescence of these crystallites across substrate steps generates screw dislocations, which produce surface steps that allow spiral growth without nucleation (31). At film thicknesses accessible with STM, i.e., <10 nm, these spirals mostly lead to cubic ice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5. For ice on Pt (111), both the surface steps and screw dislocations are critical in the formation of metastable cubic structure (and not the hexagonal one) and in the growth (24).…”
Section: Resultsmentioning
confidence: 99%
“…STM measurements were performed at T < 115 K. To avoid tip-induced damage, we kept the tunneling current <1 pA. Tip voltage was between 0.2 and 1 V. We determined the crystallographic directions of the Pt (111) substrate by evaluating the registry of atomic positions on both sides of an atomic Pt step [32,144]. All STM images presented herein are oriented in the same way relative to the substrate.…”
Section: Methodsmentioning
confidence: 99%